Closed-loop K2CO3 activation of biochar for coproduction of microporous carbon and syngas - Shen, Yafei (2024)
The current work systematically studied the technical feasibility of potassium-looping activation of biochar using K2CO3 for the coproduction of highly microporous carbon and syngas. Compared with the solid mixing method, the impregnation method showed a higher biochar activation efficiency and produced a higher quality of activated carbon. By the impregnation method, a high yield of activated carbon (60 wt %, per biochar mass) was achieved under the optimal conditions, such as an activation temperature of 800 °C, a mass ratio of biochar to K2CO3 (1:1), and a retention time of 3 h. The activated carbon with a high specific surface area (1091 m2/g) and a high microporosity (98%) was obtained. Besides, during the biochar activation process, syngas (CO/H2 molar ratio of 1.0-1.5 and yield of ∼23 wt %) was generated. The yield and surface area of activated carbon were not obviously reduced after water leaching within three cycles. The potassium-looping system was evaluated to recover and reuse biochar activation agent within subsequent cycles.